IMPLEMENTASI MODEL PEMBELAJARAN LANGSUNG DALAM MENINGKATKAN KEMAMPUAN TEKNIK DASAR PASSING BOLA VOLI PADA SISWA KELAS VII SMP NEGERI 18 PEKANBARU - Pesta Simanjuntak (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research is motivated by the observations of researchers who are also sports teachers at SMP Negeri 18 Pekanbaru on the low ability of basic volleyball passing techniques for seventh grade students of SMP Negeri 18 Pekanbaru. This study aims to improve the basic technical skills of volleyball passing through a direct learning model for class VII students of SMP Negeri 18 Pekanbaru. The subjects of this study were students of Class VII SMP Negeri 18 Pekanbaru with a total of 28 students. The form of research is classroom action research. The research instrument consisted of performance instruments and data collection instruments in the form of observation sheets for teacher activities and student activities. Based on the results of the research that has been done, several conclusions are obtained. The passing ability of class VII students of SMP Negeri 18 Pekanbaru through direct learning in the initial test obtained an average value of 66.5 (Competent Enough). In the first cycle, the students' average ability increased with an average score of 70.9 (competent). In the second cycle the students' average ability was achieved at an average value of 76.8 (Competence) with a percentage of completeness of 100%. Thus the research hypothesis which reads: Through the application of direct learning models can improve the ability of basic techniques of passing volleyball games of class VII SMP Negeri 18 Pekanbaru, can be